2008
DOI: 10.1136/emj.2006.044552
|View full text |Cite
|
Sign up to set email alerts
|

Impact of helical computed tomography in clinically evident appendicitis

Abstract: The performance of abdominal MDCT in patients with a high degree of clinical suspicion for acute appendicitis reduces the number of false positives and has the potential to reduce negative appendectomies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 26 publications
0
22
0
Order By: Relevance
“…Computed tomography (CT) is considered the most accurate imaging technique for distinguishing appendicitis from other etiologies of acute abdominal pain [6][7][8]. Recently, use of CT has improved the sensitivity of appendicitis diagnosis over ultrasound [9], Alvarado score [10], or clinical judgment [11]. Moreover, negative appendectomies have decreased from an overall rate of 20 and 40 % for women in the pre-CT era [12] to as low as 4-4.7 % overall [13,14] and 7 % for women [6] with the introduction of CT.…”
Section: Introductionmentioning
confidence: 99%
“…Computed tomography (CT) is considered the most accurate imaging technique for distinguishing appendicitis from other etiologies of acute abdominal pain [6][7][8]. Recently, use of CT has improved the sensitivity of appendicitis diagnosis over ultrasound [9], Alvarado score [10], or clinical judgment [11]. Moreover, negative appendectomies have decreased from an overall rate of 20 and 40 % for women in the pre-CT era [12] to as low as 4-4.7 % overall [13,14] and 7 % for women [6] with the introduction of CT.…”
Section: Introductionmentioning
confidence: 99%
“…5,25 Computed tomography (CT) has become the gold standard imaging modality for diagnosing acute appendicitis, with a sensitivity of 95-100% and a positive predictive value of 96%. 22,26,27 CT also enables the important differential diagnosis between complicated and uncomplicated acute appendicitis. In this study, we aimed to evaluate the feasibility of clinical history and clinical and laboratory findings in establishing the differential diagnosis between uncomplicated and complicated acute appendicitis without the use of imaging in a large, prospective patient cohort with a special interest in predicting the presence of an appendicolith.…”
mentioning
confidence: 99%
“…The analysis was performed separately across three risk strata of the Alvarado score (low risk, score 1 to 4; intermediate risk, score 5 to 6; and high risk, score 7 to 10) ( Figure 1). Within each risk stratum, each of the three main study populations, men, women and children were analysed separately [8,[10][11][12]18].…”
Section: Calibration Analysis Of the Alvarado Scorementioning
confidence: 99%
“…In patients presenting with higher Alvarado scores (cut point of 7, the criterion for surgery), pooled diagnostic accuracy results had more limited clinical value (pooled specificity for all studies 0.82, n = 29, [5,8,10,11,[18][19][20][21][22][23][24][25][27][28][29][30][31][32][34][35][36][37][38]41,42,[44][45][46][47]), with pooled specificities ranging from 0.57 for subgroup analysis of men (n = 6, [9,23,30,34,35,45] Figure S1). Overall, heterogeneity was high when all studies were included and was particularly high in the children subgroup as indicated by the variance logit transformed sensitivity and specificity (Table 2) and the prediction ellipses on the SROC curves Additional file 1 - Figure S1).…”
Section: Diagnostic Accuracy Of the Alvarado Scorementioning
confidence: 99%